Civil society in comparative perspective - Enjolras, Bernard; Sivesind, Karl Henrik, 1962- (Bingley, UK : Emerald, 2009)
This book presents a collection of comparative studies of civil society around two main issues: the comparison and analysis of civil society regimes in relation to different constructions of citizenship and welfare states and the role of civil society in governance and active participation of citizens. The first part of the book is concerned with comparisons of civil society institutional frameworks and regimes. In this section the contributions address the ways institutional cross-countries comparisons may be undertaken and discuss the extent to which common trends or divergent tendencies characterize national civil societies. The second part focuses on the role of civil society as a vector of citizens' participation and as an avenue for democracy. Democratic citizenship is often considered as requiring, in addition to a set of formal rights and obligations, a public sphere within which citizens can actively participate within and beyond the state. Building on international comparisons the articles in this section discuss the extent to and the modalities by which civil society is crucial to the functioning of democracy and the plain exercise of citizenship.
Part I. Civil society regimes and institutional framework -- The third sector in Europe : does it exhibit a converging movement? / Edith Archambault -- Civil society and new forms of governance : the case of childcare services in a European perspective / Francesca Petrella -- Public governance roles of the third sector organisations in Ireland: a comparison with South Africa / Freda Donoghue -- Toward a typology of civil society: understanding non-government public action / Chris Miller ... [et al.] -- Does public spending "crowd out" nonprofit welfare? / Karl Henrik Sivesind and Per Selle -- Part II. Civil society, citizenship and democracy -- Civil society organizations and advocacy: a comparative study between Brazil and the United States / Gabriela de Brelàz and Mário Aquino Alves -- The role of civil society organizations in different nonprofit regimes: evidence from Austria and the Czech Republic / Michaela Neumayr ... [et al.] -- Making volunteering work: the power of voluntary organizations to enhance civic skills. Some evidences from the European social survey / Rafael Vázquez-García -- Opportunity structure for citizens' participation in a European network civil society: a theoretical perspective / Bernard Enjolras -- Organized civil society, volunteering and citizenship / Thomas P. Boje -- The spirit of the civil sphere: activating static conceptions of volunteerism and citizenship / Thomas Janoski.
Includes bibliographical references.
Description based on print version record.
Keywords: Social sciences -- Comparative method; Civil society; Sociology; Social Science -- Sociology -- General